Application of Multidisciplinary Perspectives in The Study of Women’s Fiqh - Fitri Liza; Teguh Luhuringbudi; Panggih Abdiguno; Dewi Nita Utami (TATHO: International Journal of Islamic Thought and Sciences, 2025)
This research aims to identify the effective role of multidisciplinary perspectives in the study of women’s fiqh. Data collection methods included a questionnaire to 112 Madrasah Aliyah Negeri (MAN) Buleleng and one of Madrasahs Aliyah Negeri (MAN) Jakarta (whose name was not mentioned based on the request of the Head of the Madrasah in Jakarta) students, in-depth interviews, and analysis of Fiqh textbook documentation. Data were analyzed using a theoretical framework that combines Ahmed's Islamic feminism, Ainscow's inclusive education, and Crenshaw's intersectionality. Key findings reveal a gap between theoretical acceptance of menstrual rules (91.1%) and their practical implementation (82.1%), as well as the lack of representation of feminist and intersectional perspectives in the official curriculum. This study contributes to the development of a new analytical framework that integrates three theoretical approaches to understand the complexity of teaching women's fiqh. Limitations of the study include a limited sample size and a narrow focus on the issue of menstruation. Further research is recommended to expand the geographic scope, explore other aspects of women's fiqh, and conduct longitudinal studies to understand the long-term impact of women's understanding of fiqh on students' religious and social practices.